Baseline Anemia Is an Independent Predictor of Long-Term Mortality in Patients Undergoing Transcatheter Aortic Valve Implantation. (January 2022) - Baştuğ, Serdal; Çöteli, Cem; Çelik, Muhammet Cihat; Kasapkara, Haci Ahmet; Bayram, Nihal Akar; Akcay, Murat; Durmaz, Tahir
This study aimed to investigate the relationship between baseline anemia and long-term mortality in a single-center retrospective study involving patients undergoing transcatheter aortic valve implantation (TAVI). The study population included 412 consecutive patients undergoing TAVI at a center for severe aortic valve stenosis between August 2011 and November 2018. The primary end point of the study was all-cause mortality. Baseline anemia was present in 50% of our study cohort. During the median follow-up of 29 months, all-cause mortality was observed in 40.3% of the whole study population and was more frequently observed in the anemic group compared with the nonanemic group (53.5% vs 27.1%, P < .001, respectively). Cox-regression analysis revealed that Society of Thoracic Surgeons Predicted Risk of Mortality score, previous stroke, pericardial tamponade, and neutrophil–lymphocyte ratio count are independent predictors of long-term mortality after TAVI. Additionally, the presence of anemia at baseline was an independent predictor of long-term mortality with a 2.3-fold difference in the anemic group compared with the nonanemic group (hazard ratio: 2.31, 95% CI: 1.59-3.37, P < .001). Baseline anemia was observed in half of our patient population undergoing TAVI, and baseline anemia was found to be an independent predictor of long-term mortality after TAVI.